Unusual Magnetic Damping Effect in a Silver-Cobalt Ferrite Hetero Nano-System - Altbir-Drullinsky, D; Vargas-Ayala, N; Castillo-Sepulveda, S (Royal Society of Chemistry, 2015)
The static and dynamic magnetic response of the newly synthesized CoFe2O4-Ag hetero nano-system showed significant enhancement in the effective energy barrier and reduction of the magnetic hardness of CoFe2O4 upon interaction with non-magnetic Ag as compared to neat CoFe2O4. The observed magnetic properties of CoFe2O4-Ag have been dissected in detail using the superparamagnetic Stoner-Wohlfarth and Neel-Arrhenius/Vogel-Fulcher models with the aid of micromagnetic simulations. This journal is © The Royal Society of Chemistry 2015.